Party Sub‐Brands and American Party Factions. Issue 3 (20th March 2020) - Clarke, Andrew J.
Abstract: Scholars and pundits have long noted the dominance of the American two‐party system, but we know relatively little about new, endogenous institutions that have emerged within the two major parties. I argue that ideological factions provide party sub‐brands, which allow legislators to more precisely define their partisan type and capture faction‐specific resources. To support this claim, I analyze new data on nine ideological factions in the House of Representatives (1995–2018). I find that (1) faction voting is distinct, suggesting a product ripe for party sub‐branding, and (2) joining a faction changes the ideological composition of a candidate's donor base—conditional on the strength of the faction's institutions. Party sub‐branding is effective only when factions possess organizational features that induce coordinated and disciplined position taking (e.g., whips, PACs, membership restrictions). These results suggest that, even within highly polarized parties, American political ideology is more than a dichotomous choice, and factions target niche markets of political donors as a means of blunting financial instruments of party power.